An empirical study of the substitution of foreign for domestic savings in Brazil - Luiz Carlos Bresser-Pereira; Eliane Araújo; Paulo Gala (EconomiA, 2014)
This study aims to investigate the relations between the level of the real exchange rate, foreign savings and domestic savings in Brazil. The appreciation of the domestic currency caused by financing the current account deficit reduces the expected profit rate in the tradable goods industry, leading to a drop in domestic savings and the substitution of foreign for domestic savings. An econometric analysis of the Brazilian economy indicates a stable long-term relation between the exchange rate and domestic savings, and that relative devaluations of the real exchange rate positively and significantly affect domestic savings in 1994–2013. The estimations' results persist even after the period is divided into two samples, after tests showing the presence of a structural break in the model in 2002. In addition, the results of the estimations performed on the two samples confirm the presence of substitution of foreign for domestic savings. – – Este trabalho tem como objetivo investigar as relaç\~oes entre nível da taxa de câmbio real, poupança externa e poupança interna no Brasil. A apreciaç\~ao da taxa de câmbio causada pelo financiamento do déficit em conta corrente leva à reduç\~ao da taxa de lucro esperada no setor de bens comercializáveis, resultando numa queda na poupança interna, bem como na substituiç\~ao da poupança interna pela externa. A análise econométrica realizada para a economia brasileira indica que há uma relaç\~ao estável de longo prazo entre taxa de câmbio e poupança interna, e que desvalorizaç\~oes relativas da taxa de câmbio real têm impactos positivos e significantes sobre a poupança interna no período 1994–2013. O resultado das estimativas se mantém mesmo quando o período é dividido em duas amostras, seguindo testes que apontaram a existência de quebra estrutural no modelo no ano de 2002. Além disso, os resultados das estimativas para as duas amostras confirmam a existência de substituiç\~ao de poupança interna por poupança externa.
Keywords: F3; F4; O2; 330; Real exchange rate; Domestic savings; Foreign savings and economic development